Determinants of Human Resource Quality: Special Autonomy Funds, Public Spending, and Income - Qomariyah, Nur; Susilo (Journal of Development Economic and Social Studies, 2026)
Human resource quality is a crucial factor in regional development, yet Papua Province continues to record the lowest human development performance nationally despite receiving Special Autonomy Funds for more than two decades, highlighting the importance of evaluating fiscal and economic policies. This study aims to analyze the effects of Special Autonomy Funds, education spending, health spending, and per capita GRDP on human resource quality. Grounded in the Capability Approach, Human Capital theory, and Fiscal Federalism, this study employs a quantitative approach using panel data regression for the period 2019–2023. The results show that Special Autonomy Funds and education spending have positive and significant effects on human resource quality, while health spending has no significant effect. Meanwhile, per capita GRDP shows a significant negative effect, indicating that higher income levels have not fully translated into improved welfare. The findings theoretically enrich development and fiscal policy literature and provide practical implications for optimizing fund management and public expenditure allocation.